Distflow based state estimation for power distribution networks - Florez, H. A.R.; Carreno, E. M.; Rider, M. J.; Mantovani, J. R.S. [UNESP] (Springer Nature, 2018)
A new state estimation method for electrical power distribution systems using the Distflow formulation and the Weighted Least Square method to determine the steady-state operating point is presented. In order to reduce the number of measurements needed for state estimation analysis, a special set of state variables is defined. The proposed methodology is shown to be able to successfully determine the operating conditions of a electrical power distribution system with high automation levels. The proposed approach is tested on the IEEE-37 and IEEE-123 bus test system, reducing the number of state variables up to 60% when compared with conventional state estimation method.
Keywords: Distflow method; Electrical power distribution system; State estimation; State variables; Weigthed least square